2022
DOI: 10.1186/s40478-022-01411-x
|View full text |Cite
|
Sign up to set email alerts
|

Novel rapid intraoperative qualitative tumor detection by a residual convolutional neural network using label-free stimulated Raman scattering microscopy

Abstract: Determining the presence of tumor in biopsies and the decision-making during resections is often dependent on intraoperative rapid frozen-section histopathology. Recently, stimulated Raman scattering microscopy has been introduced to rapidly generate digital hematoxylin-and-eosin-stained-like images (stimulated Raman histology) for intraoperative analysis. To enable intraoperative prediction of tumor presence, we aimed to develop a new deep residual convolutional neural network in an automated pipeline and tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…The macroscopic pathological effect can be controlled by measuring the distance of the cortical access tissue to the pathologies (contrast-enhancing border or FLAIR signal) [ 23 ] and microscopically using histological methods (e.g., immuno/H&E stain, stimulated Raman histology [ 22 , 26 , 35 ]) to assess tumor infiltration (Fig. 6 e–f).…”
Section: Discussionmentioning
confidence: 99%
“…The macroscopic pathological effect can be controlled by measuring the distance of the cortical access tissue to the pathologies (contrast-enhancing border or FLAIR signal) [ 23 ] and microscopically using histological methods (e.g., immuno/H&E stain, stimulated Raman histology [ 22 , 26 , 35 ]) to assess tumor infiltration (Fig. 6 e–f).…”
Section: Discussionmentioning
confidence: 99%
“…As such, SRH imaging can be directly accepted by pathologist. Previous studies demonstrated SRH’s suitability for the analysis of freshly excised CNS surgical specimens which is particularly valuable for intraoperative pathological consultations. , Indeed, the current workflow for IC requires the sample transport to a pathology department, processing of the specimen including cytological preparations (smear or touch preps) and frozen sections, both associated with rapid HE staining of the slides and their interpretation by a neuropathologist . This conventional procedure takes 20–30 min for each sample to be processed with potential negative impact for the patient since an increase surgery duration is associated with possible complications .…”
Section: Discussionmentioning
confidence: 99%
“…In a multicenter prospective clinical trial including 278 patients, Hollon et al combined SRH and artificial intelligence (i.e., deep convolutional neural networks trained on over 2.5 million SRH images) and showed that this diagnostic method was non-inferior to pathologist-based interpretation of conventional histological images (accuracy 94.6%) [ 21 ]. Using the same artificial intelligence process, Reinecke et al demonstrated that SRH can reliably detect the microscopic presence of tumor and discriminate from non-neoplastic brain tissue in stereotactic biopsy specimens [ 49 ].…”
Section: Innovations To Increase Biopsy Diagnostic Yieldmentioning
confidence: 99%